An investigation on microstructural evolution and mechanical properties of Zn coating as interlayer on Mg-Al alloys using diffusion bonding. (2021) - Golden Renjith Nimal, R.J.; Chenthil, M.; Sangamaeswaran, R.; Hariharan, R.; Esakkimuthu, G.
Abstract: Diffusion bonding is the joining of two or more similar or dissimilar pieces of metals combined under pressure at elevated temperatures for a specific time. During the period, atoms diffuse between the two metals across the interface. The energy needed for the atomic movement entirely dependable on the stress applied and temperature. This is also extensible to non-metals, ceramics and intermetallic Compounds (IMC's). The traditional method of fusion state welding processes have some disadvantages such as the production of less heat affected zone, distortion of the base metals etc. In the present investigation, 7075 Al and AZ80 Mg alloys combined together which the effects of holding time and holding temperature are related to diffusion and are being studied for mechanical and metallurgical properties. Henceforth, the morphologies were found by optical microscopy and SEM (Li et al., 2009) [1] . Zinc coated AZ 80 magnesium combination and AA 7075 aluminum amalgam were treated to receive the preliminaries of diffusion bonding for various process parameters (Pragatheswaran et al., 2019) [10] . A bonding temperature of 350 to 450 °C, a bonding pressure of 2 MPa to 25 MPa and a holding season of 5 min to 150 min resulted in a dispersion between the zinc coated AZ80 Magnesium/AA7075 Aluminium alloys (Pragatheswaran et al., 2019) [10] . It can be noted that for the zinc coated samples the lower temperatures of 325 °C resulted in non-bonded layer and similarly at lower pressure of 2 MPa and lower time duration resulted in non-bonded layer whereas for non-coated and zinc coated layer of lower temperature resulted in better bonded nature.